An Approach to Effective Disinfection of Salon Items (clippers, combs and scissors) (The East and Central African Journal of Pharmaceutical Sciences, 2020)
Antibacterial susceptibility patterns of some bacteria isolated from selectedbarbing salons in parts of Northern Nigeria was studied for the purpose ofdeveloping a disinfectant system suitable for use in salons. The K-values forselected cells ranged from 0.0072 to 0.0399 (benzalkonium chloride), and from0.0062 to 0.1338 (propylene glycol) as against a range of 0.0147 to 0.1343 whenthe two chemicals were combined. The observed D-value range of 64.5 to 99(benzalkonium chloride), 31.5 to 105 (Propylene glycol) and 21 to 24 (admixtureof the two chemicals) were exploited in the development of "SALONSAFE" - asalon disinfectant that was able to eliminate 10\fu/ ml (of the most resistantbacterial isolated in these studies) completely in 60 seconds.
Keywords: Salonsafe, antibacterial, disinfectant, salon, K-value, D-value